Revealing the importance of suppressing formation of lithium hydride and hydrogen in Li anode protection - Gaojie Xu; Xiaofan Du; Shenghang Zhang; Jiedong Li; Shanmu Dong; Zhiwei Hu; Guanglei Cui (Interdisciplinary Materials, 2023)
Abstract The reviving of the “Holy Grail” lithium metal batteries (LMBs) is greatly hindered by severe parasitic reactions between Li anode and electrolytes. Herein, first, we comprehensively summarize the failure mechanisms and protection principles of the Li anode. Wherein, despite being in dispute, the formation of lithium hydride (LiH) is demonstrated to be one of the most critical factors for Li anode pulverization. Secondly, we trace the research history of LiH at electrodes of lithium batteries. In LMBs, LiH formation is suggested to be greatly associated with the generation of H2 from Li/electrolyte intrinsic parasitic reactions, and these intrinsic reactions are still not fully understood. Finally, density functional theory calculations reveal that H2 adsorption ability of representative Li anode protective species (such as LiF, Li3N, BN, Li2O, and graphene) is much higher than that of Li and LiH. Therefore, as an important supplement of well‐known lithiophilicity theory/high interfacial energy theory and three key principles (mechanical stability, uniform ion transport, and chemical passivation), we propose that constructing an artificial solid electrolyte interphase layer enriched of components with much higher H2 adsorption ability than Li will serve as an effective principle for Li anode protection. In summary, suppressing formation of LiH and H2 will be very important for cycle life enhancement of practical LMBs.